Halal Friendly Tourism in a non-Muslim country: Observation Study in Nepal - Menur Kusumaningtyas; Fitri Nur Latifah; Miya Dewi Suprihandari; Muhammad Syauqi (Universitas Muhammadiyah Sidoarjo, 2021)
Halal tourism is a new trend that has emerged from the rise of the halal industry. Many Muslim and non-Muslim countries hope to conquer the Muslim tourism market as the Halal market advances the tourism sector by offering tourism goods, services and infrastructure to meet their needs. Although in recent phenomena, publications and theoretical studies in this field are still limited, studies related to provisions and commitments on halal tourism and their patterns are considered lacking. Thus, the scarcity of literature and specific studies in this field is aimed at exploring and describing the concept of halal tourism in an Islamic context with special reference to the verses of the Koran and Hadith as the main sources in Islam. Meanwhile, to appreciate the existing implementation of this concept, this paper will provide a further case of the current trend of halal tourism in certain countries in Asia. This study adopted a qualitative research method using literature study and observation for data collection techniques. The results of this study include the opening of the concept of halal tourism and a comparison of cases of halal tourism in Asia, in this case Nepal as a non-Muslim country